Proposing a Conceptual-Mathematical Model for Financial Distress Prediction by Focusing on Adjusted Cash Flow Statement - Amir hosein Karbalaee karim; Yadolah Tariverdy; Ahmad YaghoobNezhad; Azita Jahanshad (راهبرد مدیریت مالی)
Bankruptcy prediction has an important status in analysis of financial situation of a firm and in the current global economy. This issue has concerned the stockholders. Thus, they are looking for solutions to identify the firms involved in crisis before occurrence of an unpleasant event and maintain primary benefits. Financial distress prediction has highly been considered by researchers in the scope of financial literature in recent years. Several studies have also been carried out in this scope. Through studying the existing theoretical principles and importance of the topic, the present survey tries to propose a mathematical model for bankruptcy prediction of companies listed in the Tehran Stock Exchange via presenting a conceptual-mathematical model and the use of a new statistical method by focusing on the adjusted cash flow statement. To this end, data of 112 companies during the time period 2011-2020 was collected and analyzed using logistic regression. The findings reveal that the effect of components of the adjusted cash flow statements on financial crisis prediction is positive and significant.